Community Participation in Improving Health in Remote Areas: A Literature Review - Dinatul Aini; Azizatul Farhaini; Bayu Karunia Putra (Peneliti.net, 2023)
This article aims to determine community participation in improving health in remote areas. This topic is important and interesting, because the health improvement plan based on the national health system aims to achieve equitable, equitable and affordable services. in the government and society can move in harmony and be beneficial for the development of health services, and from this the community really wants affordable and quality health services. The research method used is the literature review method, in which sources and data are obtained through the Publish or Perish, SINTA, and Goggle Scholar databases. In this method, the researcher uses a descriptive qualitative approach, in which this method utilizes qualitative data and is described descriptively. Data collection techniques use literature review techniques carried out by researchers to collect valid, complete, and relevant information related to the topic of the problem which is the object of research. The data analysis technique used a literature review analysis technique, in which this research was conducted by reading literary sources to obtain the necessary data. The author found that, public services are currently a hot topic of discussion in Indonesia, especially for health services in areas that are still said to be remote, because it relates to what influences community participation in improving health, especially in remote areas, namely the level of knowledge, time, and the condition of the community's social environment, therefore through socialization and education techniques all forms of information can be a solution in conveying everything related to health, so that people know and understand health efforts through community empowerment.